Erythropoietin-induced cellular differentiation requires prolongation of the G1 phase of the cell cycle. - Carroll, M (1995)
Erythropoietin (EPO), like many other hematopoietic growth factors, can induce either growth or differentiation of hematopoietic cells. Little is known about the molecular basis of this cellular decision, in part because of a paucity of cell lines in which these two phenomena can be dissociated. Ectopic expression of the EPO receptor (EPO-R) in Ba/F3, a murine interleukin 3 (IL-3)-dependent progenitor cell line, confers EPO-dependent cell growth. In these cells (Ba/F3-EPO-R), EPO also induces beta-globin mRNA, a specific marker of erythroid differentiation. Here we show that the induction of erythroid differentiation by EPO requires a delay in cell growth and a prolongation of the (G1) phase of the cell cycle. Interestingly, this effect on G1 prolongation was concentration dependent. At low EPO concentrations (0.05-0.1 unit of EPO per ml; 1 pM EPO = 0.01 unit of EPO per ml), EPO prolonged G1 and induced differentiation; at high concentrations (0.5-10.0 units per ml), EPO shortened G1 and preferentially stimulated growth. IL-3 stimulated Ba/F3 growth but not differentiation at all growth factor concentrations ranging from 0.1 to 500 pM. Moreover, IL-3 suppressed EPO-induced beta-globin induction in a dose-dependent manner. This suppression correlated with the shortening of G1 by IL-3. Taken together, these data demonstrate distinct effects of EPO and IL-3 and a balance between erythroid growth and differentiation that is cell cycle dependent.